Mechanical Property Prediction for High Early Strength Self-Consolidating Concrete - Kim, Young Hoon; Trejo, David; Atahan, Hakan N.; Hueste, Mary Beth D. (American Society of Civil Engineers (ASCE), 2012)
AbstractConcrete design codes include equations to estimate the modulus of rupture (MOR), modulus of elasticity (MOE), and splitting tensile strength (STS) of concrete based on the compressive strength. These equations have been developed based on data from normal strength conventional concrete (CC). Precast/prestressed concrete plants require that the concrete used to fabricate their structural members attain high early strength (HES). Plant conditions lend themselves to the use of self-consolidating concrete (SCC) and HES SCC could be an economical option for use under these conditions. However, limited work has been documented to determine if SCC can achieve high early strengths and limited work has been reported to determine if standard design equations are applicable for HES SCC. SCC is proportioned to achieve good flow while maintaining a homogeneous structure. To achieve this, SCC typically has to have higher paste and lower coarse aggregate volumes than CC. These conditions and the addition of new...